Pengaruh Kepercayaan Diri Terhadap Motivasi Belajar - Fitriansyah Nusi; Melizubaida Mahmud; Ardiansyah Ardiansyah; Radia Hafid; Meyko Panigoro (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The purpose of this study is to determine the effect of self-confidence on student learning motivation at Junior High School 1 Suwawa Tengah. This study uses a quantitative approach, with a Survey research method. The data used are primary data obtained from distributing questionnaires to students at Junior High School 1 Suwawa Tengah. The number of samples drawn in this study was 51 respondents. The data analysis technique used simple linear regression with the help of the SPSS program. The results of the analysis, the study showed that there was a positive and significant influence between self-confidence and student learning motivation at Junior High School 1 Suwawa Tengah. The comparison of the t-count values obtained is still greater than the t-table value so that Ho is rejected. Thus, at a confidence level of 95%, it can be concluded that there is a positive and significant influence of self-confidence on learning motivation. The coefficient of determination value of the previously obtained regression model is 0.170, this value means that 17% of the variation in learning motivation is explained by the self-confidence of a student.